1998
DOI: 10.1161/01.cir.98.18.1886
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Metabolism Limits Exercise Capacity in Patients With Chronic Heart Failure

Abstract: These results suggest that impaired muscle metabolism associated with early metabolic limitation determines exercise capacity during maximal systemic exercise in patients with CHF. There was a significant correlation between muscle metabolic capacity during systemic and local exercise in patients with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 11 publications
2
81
0
3
Order By: Relevance
“…2,[24][25][26][27][28][29][30][31][32] Decreased muscular power as well as metabolic and endocrine disorders are also known as factors of exercise limitation. 9,[33][34][35][36][37] In 1968, Zelis, et al reported a decreased vasodilatory capacity in cardiac patients. 23) Since then, a number of investigations have been made on this matter.…”
Section: Discussionmentioning
confidence: 99%
“…2,[24][25][26][27][28][29][30][31][32] Decreased muscular power as well as metabolic and endocrine disorders are also known as factors of exercise limitation. 9,[33][34][35][36][37] In 1968, Zelis, et al reported a decreased vasodilatory capacity in cardiac patients. 23) Since then, a number of investigations have been made on this matter.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the PCr concentration in muscle declines more rapidly during submaximal exercise in CHF patients indicating lower rates of oxidative phosphorylation for given absolute and relative submaximal exercise loads 6,42 . Skeletal muscle pH also began to decline earlier during exercise indicating an earlier onset of glycolysis.…”
Section: Muscle Fiber Types Muscle Biopsy Studies In Chf Have Consismentioning
confidence: 99%
“…The determinants of aerobic capacity are multifactorial, but aerobic capacity is generally believed to be impaired in the presence of abnormalities in skeletal muscle energy metabolism, 5 and energy metabolism largely depends on mitochondrial function. 6 Indeed, it has been shown that mitochondrial ATP production in skeletal muscle is impaired in insulin-resistant offspring of patients with type 2 diabetes, 7 which raises the possibility that mitochondrial oxidative phosphorylation in skeletal muscle might be impaired in MetS.…”
Section: Introductionmentioning
confidence: 99%